2017
DOI: 10.7196/samj.2017.v107i2.11451
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-associated pneumonia in South African children: Presentation, clinical course and outcome

Abstract: Background. Viruses have emerged as important aetiological agents of childhood pneumonia. Objective. To investigate the clinical presentation, severity and outcome of adenovirus-associated pneumonia (AVP) in children. Methods. A retrospective analysis of AVP cases over 12 months was performed, including demographic, clinical course and outcome (death, persistent lung disease (PLD)) data. Results. Two hundred and six AVP cases (median age 12 months, interquartile range 6 -24) were identified; 70 children (34.0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 17 publications
3
12
1
3
Order By: Relevance
“…Adenovirus was detected in almost onefourth of all study children and thus could not be associated with pneumonia. Similarly, previous studies have shown detection of adenovirus in 21 to 30% of children with pneumonia and in16% of children without any respiratory symptoms [28,45], despite adenovirus being a potential cause of pneumonia in young children [46]. We found that three-fourths of our study children with pneumonia and all children in the control group without pneumonia had acute diarrhoea.…”
Section: Discussionsupporting
confidence: 87%
“…Adenovirus was detected in almost onefourth of all study children and thus could not be associated with pneumonia. Similarly, previous studies have shown detection of adenovirus in 21 to 30% of children with pneumonia and in16% of children without any respiratory symptoms [28,45], despite adenovirus being a potential cause of pneumonia in young children [46]. We found that three-fourths of our study children with pneumonia and all children in the control group without pneumonia had acute diarrhoea.…”
Section: Discussionsupporting
confidence: 87%
“…However, there appeared to be an association between the doctor's assessment of RR at initiation of HFNC and the documented RR at transfer, with patients who were transferred remaining significantly tachypnoeic. The high proportion of infants with severe pneumonia needing transfer to L3 for respiratory support who had adenovirus on NPA supports the recently published study by Zampoli and Mukuddem-Sablay [19] demonstrating that adenovirus is an important cause of severe pneumonia necessitating ICU admission in young children in SA.…”
Section: Discussionsupporting
confidence: 77%
“…One study about risk factors associated with mortality of pneumonia children reported malnutrition was the most common factor related with fatality (24). The study of Zampoli et al in South Arica reported that ADV associated pneumonia children reported 34.0% were malnourished (25). But in our study, children with ADV infection had a lower risk of combining others disease than cases without ADV infection.…”
Section: Discussioncontrasting
confidence: 60%